JUNIOR HIGHSCHOOL STUDENTS PERCEPTIONS OF WORDWALL GAME MEDIA ON THEIR EFFECTIVENESS IN LEARNING ENGLISH THROUGH READING COMPREHENSION - Indah Aulia Syarifah; Silih Warni (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study investigates junior high school students' perceptions of Wordwall game media and its effectiveness in enhancing English reading comprehension at a junior high school Jakarta. The study highlights the urgency of improving reading skills among Indonesian learners, noting that traditional teacher-centered methods often fail to engage students effectively. Using a descriptive quantitative approach, a questionnaire was administered to 30 seventh-grade students to assess their perceptions and learning outcomes related to Wordwall. Results analyzed through PLS-SEM in SmartPLS 4 show a strong and statistically significant relationship between studentsâ€™ positive perceptions and their effectiveness in reading comprehension. A path coefficient of 0.916 and RÂ² of 0.839 suggest that perception substantially predicts learning effectiveness. The study also confirms that Wordwall's interactive and gamified features promote motivation, focus, and enjoyment in learning. These findings support integrating digital game-based tools into English language instruction to foster student-centered and engaging learning environments. The study contributes to the broader field of educational technology by offering evidence-based insights into how gamification can enhance academic outcomes in EFL contexts.